Star Wars: Comparing Military Space Power Among Major Nations - Irwan Setyawan; Fauzia Gustarina Cempaka Timur; Agus Hasan S. Reksoprodjo (Kemudi, 2025)
Advancements in space technology have significantly altered military and geopolitical dynamics worldwide. This research aims to explore the space military capabilities of major powers, specifically the United States, China, and Russia. Utilizing a qualitative method that includes literature review and case analysis, this study examines the latest developments in space technology, the military strategies employed, and the geopolitical impacts arising from competition in this domain. The findings indicate that these three countries enhance their space capabilities in different ways, such as the establishment of the Space Force by the U.S., the launch of the BeiDou navigation system by China, and the strengthening of the Aerospace Force by Russia. Additionally, this research highlights new challenges in maintaining global stability, where reliance on space technology may increase security risks. By understanding the strengths and weaknesses of each country, this study provides deeper insights into the dynamics of global power in the era of space.